The effectiveness of secondary education affirmation program (ADEM) for repatriated students in Indonesia: A case study in Lampung province on Sumatra island - I Komang Winatha; Albet Maydiantoro; Suroto Suroto; Fanni Rahmawati; Yon Rizal (Lighthouse Publishing, 2021)
The Secondary Education Affirmation Program (ADEM) for repatriated students is an effort made by the Indonesian government to provide educational services for students who have difficulties accessing education abroad. The aim of this study was to investigate the effectiveness of the government program implementation in Lampung province on Sumatera island, Indonesia. This study adopted a qualitative approach using interviews for data collection. The collected data were then descriptively analyzed. The result indicates that ADEM program is an effective way for providing access to proper education for repatriated students. However, several learning difficulties during the program implementation, such as differences in language, culture, food, and facilities, need to be taken into account. The study’s limitations with several suggestions for future research are also discussed.